An individualized musculoskeletal model for the analysis of amputee running - Kersting, U.; Gurney, J.; Lewis, S.; Rasmussen, S. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
The purpose of this study was to develop and apply a three-dimensional full body model for the analysis of transtibial amputee athletes. Sprint running was used as an example with a female sprinter as a subject. Data were collected on a running track leading through a biomechanics laboratory with two force platforms in the runway. Inverse dynamics were calculated using a basic and an advanced model, the latter including detailed information on all important muscle groups. Results support what was published on submaximal running with regard to joint moments and power. The muscle model revealed highly asymmetric muscle forces around the hip joint which may explain the overuse injuries some of these runners experience. Future research is needed to improve the individualisation of the modeling approach.